Users’ intentions towards perceived risks on Internet SNS -base on Facebook and Wretch - Lo, Po-Wen (2009)
With the rapid growth of the Internet over the past few years, people are relying more and more on the services it provides, such as online shopping, online chatting or online delivery. People can easily communicate or exchange information with friends online without any physical boundaries, and because of the convenience of the Internet, more and more Internet SNS are being launched to attract young people, and these have become one of the most popular pastimes of the current generation.